Soft actuated material: Exploration of a programmable composite. (March 2021) - Kieffer, Lynn Hyun; Nicholas, Paul
This paper describes the development of a programmable composite material and investigates its application in architecture as flexible and controllable surfaces. The composite leverages qualities found in the field of soft robots, that is, strength, precision, and the ability to change shape through vacuum actuation. It is an exploration of a range of applications for shape shifting composites within different phases of architecture. This research has deployed a controlled form-actuator of a designed surface as a reusable and flexible approach for concrete formwork and as a continuously changing spatial element, which aims to create a more engaging relationship between habitat and inhabitant. The design method linked to this composite aims to converge technology and material behavior and therethrough create a more linear process from design to construction. This paper elaborates on the design, simulation and fabrication methods, and their development through empirical research from individual actuatable cells to a controllable multi-cell surface and associated design tool.